Design and Analysis of a Natural Gas-Fueled Flameless Hot Air Generator - Valarie Kaksing Baraok; Amirnordin, Shahrin Hisham; Adam Kasani; Amir Khalid; Mohd Faizal Mohideen Batcha; Mzahar Abd Jalal; Makatar Wae-hayee; Khairul Effendy Ahmad Zainudin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The process of flameless combustion relies on the recirculation of exhaust gas, which prevents the generation of nitrogen oxides (NOx) while maintaining the system’s high level of thermal efficiency. The term “re-circulated exhaust gas” refers to the exhaust gas that is used in flameless combustion and is defined as the exhaust gas that is re-circulated and mixed with the combustion air prior to the reaction. Alternatively stated, natural gas is not a renewable resource. Due to energy demands, this is a significant challenge for humanity. It cannot be refilled once they’ve been depleted. On the other hand, natural gas is both environmentally and economically favourable. The use of flameless combustion helps address pollution and stability concerns. In addition to reducing emissions, this research can aid in minimising consumption and, more crucially, lowering regulations for harmful exhaust emissions. Therefore, the goal of this study is to design a laboratory-scale flameless hot air generator fuelled by NGV gas fuel. SolidWorks is used to create a cylindrical shape flameless hot air generator and to analyze the thermal analysis of operating temperature range of 800°C to 1200°C. The simulation result of the thermal analysis showed that the refractory ceramic layer can store and maintain heat. Results from previous studies found that when flameless combustion temperature increases, emissions drop. This study will help to demonstrate Flameless Hot Air Generator (F- HAG) design and flameless combustion emissions to reduce pollutant emissions.